Increased Knowledge of General Practitioners Gunungsitoli Regional Hospital regarding Visum Et Repertum - Petrus, Asan; Gafar, Abdul; Prayugo, Bambang; Hidayat; Pase, M.A (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Based on a survey we conducted in November 2019 at Gunungsitoli Regional Hospital regarding visum et repertum of bodies that were not good quality, this activity aimed to improve the skills of general practitioners at Gunungsitoli Hospital, especially those on duty in the Emergency Unit in making reports in the form of visum et repertum. with good quality. The method is implemented in the form of a lecture followed by a question and answer. Results: Based on interviews, questions and answers, observations and pre-test results (mean score of 58) and post-test (mean score of 86), during the activity, the results of the increase in understanding of general practitioners at Gunungsitoli Hospital in making visum et repertum. With a good visum et repertum report, it will make clear an incident of a criminal act that occurred so that the settlement of the case in court gives the fairest possible decision.